Chinese herbal medicines in the prevention and treatment of chemotherapy-induced nausea and vomiting. Issue 2 (June 2018) - Lv, Chang; Shi, Chengjin; Li, Lifen; Wen, Xuesen; Xian, Cory J.
Abstract : Purpose of review: Chemotherapy-induced nausea and vomiting (CINV) critically impact on cancer patients' quality of life, causing various complications, and increasing the risk of chemotherapeutic failure. Current treatments addressing CINV are reasonably costly and have many side effects. Chinese herbal medicines (CHMs) have been widely used in treating CINV in China. Clinical trials and modern experimental studies on CINV using CHMs are reviewed for clues that may help us to better prevent and treat CINV with CHMs, and develop safe and effective treatments. Recent findings: Since 1985, 92 clinical trials on CINV were identified, which comprised of 3778 patients with different cancer types, chemotherapy regimens, prescriptions, treatment durations, and combinations with Western medicines. The most frequently used herbs are Pinellia Rhizoma, Glycyrrhizae Radix et Rhizoma, Poria, and Atractylodis Macrocephalae Rhizoma, aiming to regulate the flow of Qi and remove phlegm and dampness residing in the stomach and spleen. Although all of the reported trials are randomized open trials, the curative effects range from 55.81 to 100%. Summary: CHMs seem effective in the prevention and treatment of CINV based on the clinical trials and some animal experiments, although the scientific validity of many clinical studies remain to be confirmed as many of them were inadequately designed. Further well designed clinical trials and more preclinical studies with reliable markers are required to confirm the usefulness of CHMs as complementary medicines for treating CINV and to use CHMs as rational prescriptions rather than based only on empirical knowledge. Abstract : Supplemental Digital Content is available in the text